N-{4-[(3,4-Dimethylphenyl)sulfamoyl]phenyl}acetamide - Khan, I.U.; John, P.; Khizar, S.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit of the title compound, C(16)H(18)N(2)O(3)S. Small but significant twists about the (S)N-C and S-C bonds differentiate the molecules but the most obvious difference is found in the relative orientation of the meta-methyl groups, which lie on opposite sides of the molecules. Overall, both molecules adopt a U shape but with significant twisting evident, particularly in the second independent molecule [dihedral angles between benzene rings = 63.90 (13) and 35.78 (11)degrees]. In the crystal, N-H...O hydrogen bonds lead to supramolecular chains with a tubular topology propagating in [100] and C-H...O contacts cross-link the chains.